Regulamentação e concepção das bibliotecas dos Institutos Federais de Educação, Ciência e Tecnologia : em busca de sua historicidade e identidade - Santos, Maria Aparecida Brito (2017)
The history of the libraries of the Federal Institutes of Education, Science and Technology – IFs – is related to emergence of the latter, reflecting the historical trajectory of each institution. Their distinctive structure and school space full of diversity and specificities, in addition to the offer of education in different levels and modalities of teaching, directly influenced the organization and development of the libraries. Thus, the objective of this research is to understand the conception of these libraries before the educational, social and legal context of the IFs, in order to ascertain how their identity is being constructed before context exposed. To do that, an exploratory and documentary research was developed, in which a bibliographical survey on the history of professional technological education in Brazil and the history of the creation of the Federal Institutes was carried out, together with a documentary analysis on the main laws, institutional development plans of each IF, regiments and regulations of their libraries. From the results, it is possible to verify that: the libraries of the institutions of professional and technological education are included for the first time when, through Decree No. 5,773/2006, the Federal Centers of Technological Education - CEFETs - are authorized to offer higher education; With the creation of the IFs in 2008, through Law No. 11,892, the library is presented in all records as a mandatory sector, with no clear association to its pedagogical support function and is structured in the light of instruments and policies aimed at higher education.